3D‐Non‐destructive Imaging through Heavy‐Metal Eosin Salt Contrast Agents. Issue 14 (5th February 2021) - Busse, Madleen; Marciniszyn, Jaroslaw P.; Ferstl, Simone; Kimm, Melanie A.; Pfeiffer, Franz; Gulder, Tanja
Abstract: Conventional histology is a destructive technique based on the evaluation of 2D slices of a 3D biopsy. By using 3D X‐ray histology these obstacles can be overcome, but their application is still restricted due to the inherently low attenuation properties of soft tissue. In order to solve this problem, the tissue can be stained before X‐ray computed tomography imaging (CT) to enhance the soft tissue X‐ray contrast. Evaluation of brominated fluorescein salts revealed a mutual influence of the number of bromine atoms and the cations applied on the achieved contrast enhancement. The dibromo fluorescein barium salt turned out to be the ideal X‐ray contrast agent, allowing for 3D imaging and subsequent complementing counterstaining applying standard histological techniques. Abstract : Add some color : The dibromo fluorescein barium salt proves to be a suitable staining agent enabling the diagnostic screening of tissue samples by X‐ray microscopic computed tomography without impending further diagnostics through histological methods.